2014
DOI: 10.5301/hipint.5000110
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion Fractures Involving the Straight and Reflected Heads of the Rectus Femoris

Abstract: Tumours and sport injuries can both affect active, young patients, and the symptoms of the two often overlap. Neglected avulsion injuries sometimes cause a mass to develop which can mimic a tumour. We discuss the diagnosis, treatment, and results following nine anterior inferior iliac spine (AISS) avulsion fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Nonoperative treatment consisting of analgetics, limited activities, and partial weight bearing using crutches for at least 3–6 weeks has shown to be successful in many of these injuries [3, 21, 23, 2527]. Metzmaker et al presented successful nonoperative treatment of 27 avulsion fractures using a 5-phase rehabilitation protocol with full return to sports not until 2 months after injury [3].…”
Section: Discussionmentioning
confidence: 99%
“…Nonoperative treatment consisting of analgetics, limited activities, and partial weight bearing using crutches for at least 3–6 weeks has shown to be successful in many of these injuries [3, 21, 23, 2527]. Metzmaker et al presented successful nonoperative treatment of 27 avulsion fractures using a 5-phase rehabilitation protocol with full return to sports not until 2 months after injury [3].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 83 avulsions, 63 (75.9%) occurred in male patients, 4(4.8%) in female patients and 16(19.2%) failed to specify gender. The mean age at the time of injury ranged from 14 19,20 e31.8 years, 22 with a mean age across all studies of 22.2 years. The sporting activities commonly practised were soccer and American football.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The mean duration from onset of symptoms until diagnosis ranged from one day 7 to 90 days. 20 The most common reported symptom was pain during hip flexion.…”
Section: Preceding Historymentioning
confidence: 99%
“…Uzun et al reported nine patients with avulsion fractures of the AIIS who sought treatment at a mean of 3 months after the initial injury. 21 Radiographs, CT, and MRI were performed, and activity modification and physical therapy were initiated. Even in these nine patients conservative treatment led to an excellent outcome, and follow-up radiographs showed a significant decrease in the size of the ossified masses.…”
Section: Anterior Inferior Iliac Spinementioning
confidence: 99%